Kepadatan Populasi Kepiting Rajungan (Portunus pelagicus L.) Di Teluk Buo Kecamatan Bungus Teluk Kabung Padang Sumatera Barat - Santoso, Sugeng; Nurhadi, Nurhadi; Lusi, Armein (STKIP PGRI Sumbar, 2013)
ABSTRACT Swimming crab is a commodity of sea that have economical value, because of that the fishermen did overfishing. The fishermen do not think the effect of wiped out of swimming crab and low reproduction from crab that cause the population of crab at Gulf Buo become. In addition, the fishemen found problem so, the population of fishemen become decrease. it happened beause of the instrument still traditional. the research is to know the density population of Swimming crab and chemical physics factors at Gulf Buo Padang West Sumatra. The research did on July to Agust 2013 at Gulf Buo Bungus District Bay Kabung Padang West Sumatra. Sample took by using descriptive, crabs arrested by using a tunnel set, the assembling of snare by choosing location based on the differentiante of subtrat.traps captured using the tool, trapping by selecting locations based on different subtrat. The results of research that has been conducted with a population that is:1.2 individuals / snare. Parameters of chemical physics factor Temperature 29-300C, Salinity 24.4-33 ppt, pH 7, DO 1.73 - 3.12 ppm.